2021
DOI: 10.1002/hbm.25590
|View full text |Cite
|
Sign up to set email alerts
|

Exploring brain connectivity changes in major depressive disorder using functional‐structural data fusion: A CAN‐BIND‐1 study

Abstract: There is a growing interest in examining the wealth of data generated by fusing functional and structural imaging information sources. These approaches may have clinical utility in identifying disruptions in the brain networks that underlie major depressive disorder (MDD). We combined an existing software toolbox with a mathematically dense statistical method to produce a novel processing pipeline for the fast and easy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 89 publications
(154 reference statements)
0
13
0
Order By: Relevance
“…Specifically, VAN is involved in top-down controlled attentional selection and bottom-up attentional processing through dynamic interaction with DAN (Geng and Vossel, 2013;Vossel et al, 2014), thus mediating externally oriented attention, cognitive and emotional regulation (Kaiser et al, 2015;Mao et al, 2020;Stumme et al, 2020). Previous studies had proved that abnormal function of VAN was implicated in several psychiatric disorders such as major depressive disorder and adolescent depression (Liu et al, 2019;Ayyash et al, 2021). The activation of VAN was triggered in response to violation of expectation, thereby reorienting to environmental stimuli, driving learning, reward, or affective mechanisms (Corbetta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, VAN is involved in top-down controlled attentional selection and bottom-up attentional processing through dynamic interaction with DAN (Geng and Vossel, 2013;Vossel et al, 2014), thus mediating externally oriented attention, cognitive and emotional regulation (Kaiser et al, 2015;Mao et al, 2020;Stumme et al, 2020). Previous studies had proved that abnormal function of VAN was implicated in several psychiatric disorders such as major depressive disorder and adolescent depression (Liu et al, 2019;Ayyash et al, 2021). The activation of VAN was triggered in response to violation of expectation, thereby reorienting to environmental stimuli, driving learning, reward, or affective mechanisms (Corbetta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The goal was to evaluate whether network-level differences can be detected (1) between REM and NREM groups at baseline, (2) between REM and NREM groups at week-8, and (3) within the REM group between baseline and week-8. We applied a FATCAT-awFC pipeline, developed in our previous work ( Ayyash et al, 2021 ), that involves the combination of the Functional and Tractographic Connectivity Analysis Toolbox ( FATCAT ) ( Taylor and Saad, 2013 ) with a computationally intense method, known as the Anatomically-Weighted Functional Connectivity ( awFC ) method ( Bowman et al, 2012 ). Our previous work ( Ayyash et al, 2021 ), identified that combining metrics from different modalities in a multiplicative manner, provides robust findings whereby the cost associated with the weaker modality is reduced and significant patterns are highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the macroscopic connectome is a blend of structural and functional connectivity, combining structural and functional connection in a data fusion approach may provide a better representation of the complex human connectome. While the FATCAT-awFC pipeline was first introduced in Ayyash et al (2021) , here we explore the utility in applying a data fusion approach to study brain changes associated with development. This article extends our previous work by applying the method to study brain connectivity within RSNs in a sample of children aged 7–9 years old.…”
Section: Introductionmentioning
confidence: 99%